Sikh women diaspora in Malaysia: the reality of their role and status in the religious domain - Kaur, Charanjit; Gill, Sarjit Singh (Sage Publications, 2018)
This article aims to examine how the Sikh women diaspora from two generations exercised their rights within the religious domain in Malaysia. Sikhism has a unique world view of gender ideology; from a gender perspective, God is symbolically described as a husband to all of humanity, whereby all humans, irrespective of gender, are perceived as having the status of wives to God. Since the Sikh religion focuses on the concept of the spirit rather than the physical body; therefore, the position of God and mankind should be cognized from the viewpoint of transformation of spirit. Most significantly, every human being, be they male or female, is held in equal importance, with each individual being conferred the same position, status, rights and opportunity to live this life as God has ordained. In fact, tenets of life that define practices as being praiseworthy, or to be avoided, are not gender specific. This makes the philosophy of gender equality of the Sikh religion particularly interesting and worthy of academic scrutiny. To what extent is it true that women have equal status with men? The authors discovered that patriarchal cultural practices have clearly dominated Sikh women’s views about their roles in daily life, as well as in the perception of their own status. This article concludes with specific recommendations to uplift and strengthen gender equality among the Sikh community in the religious domain.